Abordagem via integrais de trajetória do processo de troca e dissipação de energia num sistema composto por dois osciladores harmônicos dissipativos acoplados - o modelo duplicado de Caldeira & Leggett - Cacheffo, Alexandre (Universidade Federal de São Carlos, 2005)
In this work, we analyse the dissipation and interchange of energy in a system composed by two harmonic oscillators, each one associated with a thermal reservoir. To this end, we employ the Caldeira & Leggett approach, based on path integral formulation, to obtain the time evolution of the reduced density operator of the system composed by both oscillators.
Keywords: Mecânica quântica; Dissipação de energia; Decoerência (decoherence); Integrais de trajetória; Óptica quântica; CIENCIAS EXATAS E DA TERRA::FISICA